Tasting French terroir : the history of an idea - Parker, Thomas, 1969- (California studies in food and culture, 2015)
"This book explores the origins and significance of the French concept of terroir, demonstrating that the way the French eat their food and drink their wine today derives from a cultural mythology that evolved between the Renaissance and the Revolution. Through close readings and an examination of little-known texts from diverse disciplines, Thomas Parker traces terroir's evolution, providing a privileged insight into how gastronomic mores were linked to aesthetics in language, gardens, and painting and how the French used the power of place to define the natural world, explain comportment, and frame France as a nation"--Provided by publisher.